Business Incubators and Technology-Based Startups in Emerging Economies: A Bibliometric Analysis - Prima Fithri; Alizar Hasan; Donard Games; Berri Brilliant Albar (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2025)
In the context of rapid technological advancement and the global rise of entrepreneurship, business incubators have become essential mechanisms for supporting technology-based startups, particularly in emerging economies. These incubators play a strategic role in bridging resource gaps, fostering innovation, and enhancing the survival and growth of early-stage ventures. Despite their increasing importance, there remains a limited understanding of how incubator performance directly influences startup outcomes. This study addresses that gap through a comprehensive bibliometric analysis of 920 scholarly articles published between 2010 and 2022, sourced from Scopus and Google Scholar. Using VOSviewer, the analysis identifies key research trends, influential publications, and thematic clusters related to incubator performance. The findings reveal a significant increase in research activity over the past decade, with a peak in 2018, and a strong concentration of publications in journals focused on technology transfer and innovation management. Prominent themes include academic entrepreneurship, incubator performance, technology transfer offices, and the role of innovation ecosystems involving academia, industry, and government. These themes highlight the multifaceted nature of incubator success and the importance of cross-sector collaboration. The study also emphasizes the need for integrated evaluation frameworks to enhance incubator effectiveness and guide institutional and policy-level strategies. The novelty of this research lies in its synthesis of bibliometric insights to propose future research directions and methodological improvements for assessing incubator performance. By mapping the intellectual landscape of incubator research, this study contributes to a deeper understanding of how incubators can be optimized to support sustainable startup development and economic growth in emerging markets.